Multichannel Digital Marketing Optimization through Big Data Analysis in the Tourism Industry - Hidayat Hidayat; I Made Indra P; Nova Christian Mamuaya; Darwin Damanik; Farida Akbarina (International Journal of Artificial Intelligence Research, 2022)
In today's information-saturated environment, the travel and tourism industry is increasingly dependent on technology to attract new customers. Therefore, what kinds of digital marketing techniques must be put into action in the tourism business to draw in customers and establish a digital brand name? In this section, the author will address research on how to maximize the effectiveness of multichannel marketing in the tourism industry by making use of big data. This investigation takes a qualitative approach and makes use of descriptive research tools. According to the findings, in contrast to the websites of other industries, such as the manufacturing and logistics industries, where customers want to get answers to their questions as quickly as possible and then leave the web page, tourism websites find it more profitable to keep the attention of customers on their websites for longer periods to increase their visibility. As a result, organizations involved in tourism employ multichannel marketing with the assistance of big data to plan marketing campaigns, provide assistance in making the appropriate decisions, create innovations, and personalize customers.